Pharmacological basis for the medicinal use of cardamom in asthma (Bangladesh Journal of Pharmacology, 2011)
Cardamom (Elettaria cardamomum) is widely used in folk medicine for the treatment of asthma. This study describes its airways relaxant potential, with elucidation of possible underlying mechanism. Crude extract of cardamom which tested positive for alkaloids, flavonoids, saponins, sterols and tannins, when tested against carbachol-mediated bronchoconstriction in rats under anesthesia, it dose-dependently (10-100 mg/kg) suppressed the carbachol (1 µmol/kg)-evoked increase in the inspiratory pressure. In isolated rabbit trachea tissues, crude extract of cardamom caused relaxation of both carbachol (1 µM) and high K+ (80 mM)-induced contractions, like that caused by verapamil, suggesting its Ca++ channel blockade action. These results indicate that cardamom exhibits bronchodilatory effect, mediated through Ca++ antagonist mechanism, which provides sound mechanistic background for its medicinal use in asthma.